MiR-181b Inhibits the Proliferation of Lymphoma Rajixi Cell Line by Regulating the Expression of Target Gene FAMLF - Lu, Jingyan; Huang, Xiaohong; Wang, Linna; Li, Yunqian (Cellular and Molecular Biology, 2022)
ALCL is an aggressive lymphoma. In most cases, it is diagnosed as stage II or IV in the initial diagnosis, but it has a good response to concurrent chemotherapy with epinephrine. The six-year survival rate is about 50%. This study focused on miR-181b inhibiting the proliferation of the lymphoma Rajixi cell line by regulating the expression of the target gene FAMLF. Observe the morphology of HE with an optical microscope. Immunohistochemical staining was performed on a series of lymphocyte surface markers and cytotoxic granular membranes. In 28ALCL cases, PCR detection of immunoglobulin and T cell receptor gene recombination was performed. Summarize the characteristics of ALCL clinical pathology and the main points of diagnosis and differential diagnosis in daily business, summarize the characteristics of ALK-positive and the cytotoxicity of ALCL, and conduct a preliminary investigation on the cell source, pathological organization and tumor classification. Only four ENBAI subtypes, v-Val, P-THR, V-leu, and P-ALA were detected in lymphoma tissue, and no V-Pro subtype was found. Of the 110 positive lymphomas, 107 were single-digit Rajixi 18 (33%), and the remaining 1 (14%) were double-infected Rajixi. The results show that miR-181b can inhibit the proliferation of the lymphoma Rajixi cell line by regulating the expression of the target gene FAMLF.